Persistant versus late onset among female offenders: a test of state dependent and population heterogeneity interpretations - Gunnison, Elaine (Western criminology review, 2010)
Research into female offending has begun to explore the utility of different offending trajectories for females. The current research extends this new line of inquiry by employing both population heterogeneity and state dependent interpretations of offending. Using data on a sample of females collected from a southwestern prison, the results indicate that there are significant differences between persistent and late onset offenders. While many theoretical variables did not distinguish between late onset and persistent offenders, sexual abuse did. This research further suggests that prior sexual abuse may be a key factor in explaining the persistence of female offending. Additionally, substance abuse problems and affiliation with deviant peers were also important factors in explaining female persistence. The results also find support for both population heterogeneity and state dependent approaches to understanding female criminality.